SalesForce Competency Development Model (Sales) in the Digital Age - Septiana, Sany Mega; Suryanto, Suryanto (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to analyze how the sales force competency development model (Sales) in the digital age. The research method used in this study is to use a qualitative method by conducting interviews with 2 subjects who are salespeople in a department store. Based on the results of research that has been done show that the sales force competency development model (sales) in the digital era has implemented the Generic Competency Model for Salespeople from Spencer & Spencer. This competency model consists of twelve generic competencies. The suggestion from researchers is that as a salesperson who is the spearhead of the company, a salesperson is expected to be able to continue to improve their competencies, this can be done by transferring knowledge through training, or learning through other media that can support their competencies in doing so. product selling and increasing their performance.